Dignidad Entre Rejas: Una mirada crítica al sistema carcelario en Brasil - Burbano Herrera, Clara; Moreira Gouveia, Kristal (Pontificia Universidad Católica del Perú, 2025)
This article presents a critical analysis of the current situation of persons deprived of liberty in Brazil, exploring the reasons why prison conditions fail to protect the dignity of these individuals and do not meet international human rights standards. We argue that the deplorable situation in Brazilian prisons is the result of a series of deficiencies on the part of the State, both in terms of negligence in implementing criminal procedural legislation and in criminal policy decisions grounded in social marginalisation and necropolitics. We argue that the inhuman conditions in prisons are the outcome of a deliberate political decision. Our theoretical analysis is based on the work of Achille Mbembe, who asserts that necropolitics is the power exercised by the State, through its institutionalised structures, to determine which bodies are deemed disposable in society, relegating vulnerable groups to death through neglect or active persecution, disguised as institutional actions.

Este artículo presenta un análisis crítico de la situación actual de las personas privadas de libertad en Brasil, explorando las razones que explican por qué las condiciones carcelarias distan de proteger la dignidad de estas personas y de cumplir con los estándares internacionales de derechos humanos. Sostenemos que la situación deplorable en las prisiones brasileñas es consecuencia de una serie de deficiencias por parte del Estado, tanto en lo que respecta a la negligencia en la implementación de la legislación procesal penal como en las decisiones de política criminal fundamentadas en la marginación social y la necropolítica. Argumentamos que las condiciones inhumanas en las prisiones son el resultado de una decisión política deliberada. Nuestro análisis teórico se basa en el trabajo de Achille Mbembe, quien afirma que la necropolítica es el poder ejercido por el Estado, a través de sus estructuras institucionalizadas, para dictar qué cuerpos son desechables en una sociedad, relegando a los grupos vulnerables a la muerte mediante la negligencia o acciones de persecución activas, disfrazadas de acciones institucionales.
The Dignity of Persons Deprived of Their Liberty: An Analysis of Prison Conditions in Brazil
Keywords: Human Rights; Prisons; People deprived of liberty; Brazil; Human dignity; Derechos Humanos; Prisiones; Personas privadas de la libertad; Brasil; Dignidad humana; https://purl.org/pe-repo/ocde/ford#5.05.00